Married women pre-marital HIV testing status in Ethiopia: Individual and community level factor analysis - Birhanu, Molla Yigzaw; Ketema, Daniel Bekele; Desta, Melaku; Habtegiorgis, Samuel Derbie; Mengist, Belayneh; Alamneh, Alehegn Aderaw; Abeje, Ayenew Negesse; Tegegne, Eniyew; Mengist, Aytenew Geremew; Dessalegn, Migbar; Bekele, Getamesay Molla; Jemberie, Selamawit Shita (Frontiers in Medicine, 2023)
Introduction Marriage with serodiscordant couples accounts for 65–85% of new infections. Pre-marital HIV testing opens the door for HIV infection prevention and control. So, pre-marital HIV testing is essential to fully enjoy the right to marry and start a family but there is no information regarding pre-marital HIV testing at the community level in Ethiopia. Methods: This study was conducted using 10008 samples of data extracted from EDHS, 2016. To identify individual and community level factors a multi-level binary logistic regression model was used. Among fitted models, full model was taken as the best model using AIC. To declare the presence or absence of significant association, a p-value <0.05 with CI was used. Results: In Ethiopia, 21.4% (95% CI: 20.6, 22.2%) of study participants had pre-marital HIV testing. Age 35 to 49 years (AOR = 0.25; 95% CI: 0.09, 0.66), educated (AOR = 1.76; 95% CI: 1.17, 2.79), and rich (AOR = 1.95; 95% CI:1.13, 3.55), having media exposure (AOR = 1.54; 95% CI: 1.30, 4.71) and high community level literacy (AOR = 0.38; 95% CI: 0.22, 0.66) were factors associated significantly. Conclusion: Pre-marital HIV testing practices in Ethiopia are insignificant in order to eliminate HIV/AIDS epidemic by 2030. Age 35 to 49 years, high community-level literacy, rich, and having media exposure were factors associated significantly. Increase information dissemination for creating awareness as well as given the human rights and public health implications, the policymakers should make “pre-marital HIV testing as mandatory”.